Secure VLSI Design: Countermeasures against Hardware Trojans and Side-Channel Attacks - Khair, Md Abul; Ande, Janaki Rama Phanendra Kumar; Goda, Dileep Reddy; Yerram, Sridhar Reddy (Engineering International, 2019)
To counter the growing risks to the integrity of integrated circuits (ICs) from side-channel assaults and hardware Trojans, secure VLSI design is essential. This research aims to understand better how to defend against these attacks by strengthening the security posture of VLSI-based systems. Using a thorough methodology, the study combines rigorous validation procedures, practical implementation strategies, and early integration strategies to create robust security measures. Key conclusions emphasize the significance of proactively integrating countermeasures, utilizing reliable hardware modules, and implementing appropriate validation procedures to manage risks successfully. The value of industry collaboration, regulatory frameworks, and education programs in promoting secure VLSI design techniques is highlighted by policy implications. Stakeholders can improve the security posture of electronic devices, protect vital infrastructure, and guarantee the reliability of VLSI-based systems in an increasingly linked world by addressing constraints and regulatory consequences.